At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's solve the given equation step-by-step without using the Python code reference and ensuring the solution is presented as if derived by manual calculations.
Given the equation:
[tex]\[ 4(2x - 3) = 9 - 3(2 + x) \][/tex]
Let's simplify and solve it step-by-step:
1. Distribute the constants inside the parentheses:
[tex]\[ 4 \cdot (2x) - 4 \cdot 3 = 9 - 3 \cdot 2 - 3 \cdot x \][/tex]
[tex]\[ 8x - 12 = 9 - 6 - 3x \][/tex]
2. Simplify the terms on both sides:
[tex]\[ 8x - 12 = 3 - 3x \][/tex]
3. Move the terms involving [tex]\( x \)[/tex] to one side and the constant terms to the other side. Add [tex]\( 3x \)[/tex] to both sides:
[tex]\[ 8x + 3x - 12 = 3 \][/tex]
[tex]\[ 11x - 12 = 3 \][/tex]
4. Add 12 to both sides to isolate the [tex]\( x \)[/tex]-terms:
[tex]\[ 11x - 12 + 12 = 3 + 12 \][/tex]
[tex]\[ 11x = 15 \][/tex]
5. Divide both sides by 11 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{15}{11} \][/tex]
So the solution to the equation [tex]\( 4(2x - 3) = 9 - 3(2 + x) \)[/tex] is:
[tex]\[ x = \frac{15}{11} \][/tex]
Given the equation:
[tex]\[ 4(2x - 3) = 9 - 3(2 + x) \][/tex]
Let's simplify and solve it step-by-step:
1. Distribute the constants inside the parentheses:
[tex]\[ 4 \cdot (2x) - 4 \cdot 3 = 9 - 3 \cdot 2 - 3 \cdot x \][/tex]
[tex]\[ 8x - 12 = 9 - 6 - 3x \][/tex]
2. Simplify the terms on both sides:
[tex]\[ 8x - 12 = 3 - 3x \][/tex]
3. Move the terms involving [tex]\( x \)[/tex] to one side and the constant terms to the other side. Add [tex]\( 3x \)[/tex] to both sides:
[tex]\[ 8x + 3x - 12 = 3 \][/tex]
[tex]\[ 11x - 12 = 3 \][/tex]
4. Add 12 to both sides to isolate the [tex]\( x \)[/tex]-terms:
[tex]\[ 11x - 12 + 12 = 3 + 12 \][/tex]
[tex]\[ 11x = 15 \][/tex]
5. Divide both sides by 11 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{15}{11} \][/tex]
So the solution to the equation [tex]\( 4(2x - 3) = 9 - 3(2 + x) \)[/tex] is:
[tex]\[ x = \frac{15}{11} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.